A multiphysics model for the thermoelectric dissociation of gas hydrates. (1st January 2023) - Zohdi, T.I.; Moridis, G.J.
Abstract: This work develops a model and rapid simulation strategy for the electrically-driven dissociation (unlocking) of subsurface gas hydrates. There are two schools of thought, as to how electrical fields can dissociate gas hydrates: Case 1 : gas hydrates are dissociated (unlocked) by an appropriate intensity and frequency of the electric field, Case 2 : gas hydrates are dissociated by an appropriate level of Joule heating. In either case, one must resolve the thermoelectric fields within a heterogeneous medium consisting of encapsulated gas hydrates in a interstitial material. Accordingly, the objective of this work is to develop an easy-to-calibrate model and rapid simulation strategy to guide the delivery of an appropriate current and electrical field, as well as an appropriate level of Joule heating. The approach utilizes a coupled system of equations based on: (1) an electrical-flow submodel, (2) a thermal field evolution submodel, (3) a thermoelectric and frequency-dependent attenuation and (4) a spatio-temporal Finite-Difference Time Domain (FDTD) discretization of the coupled field equations. The model can be rapidly computed and allows analysts to vary parameters quickly, which facilitates the potential use of Machine Learning paradigms for data-model calibration. Numerical studies are provided to illustrate the behavior of the model.